Screening of bioactive compounds of sirih leaves (Piper betle L.) as antibiofilm against the glucosyltransferase of Streptococcus mutans enzyme - Elfi Zahara; Frengki Frengki; Sheila Fadillah; Daniel (Universitas Ahmad Dahlan, 2026)
Dental caries primarily caused by Streptococcus mutans biofilm, and the critical role of the glucosyltransferase (Gtf) enzyme in its pathogenicity necessitates the search for safer natural alternatives to conventional chemical agents like chlorhexidine. The traditional